EVALUASI NILAI BIOLOGIS KALSIUM DAN FOSFOR YANG DIBERIKAN PAKAN LENGKAP, TEBON JAGUNG DAN RUMPUT RAJA PADA TERNAK SAPI FRIES HOLLAND (FH) - Kogouw, Bella Mariance; Tulung, Y.L.R.; Tuturoong, R.A.V.; Rumambi, Agnitje (ZOOTEC, 2020)
EVALUATION THE BIOLOGICAL VALUES OF CALCIUM AND PHOSPHORS TO GIVED COMPLETE FEED, CORN FORAGE, AND KING GRASS IN FH (fries Holland).Â  This study aims to evaluate the biological value of calcium and phosphorus given complete feed, corn forage and king grass in FH (Fries Holland). The material used were 14 FH dairy cattle 7-8 years old, body weight 300-400 kg. The cages used were individual cages. The feed given were corn forage, king grass and concentrates. The analysis of t-test data (t-test two samples unequal variances) was used in this study, consisting of 2 types of treatment and 7 replications. They were Ra = 70% corn forage + 30% concentrate and Rb = 35% corn forage + 35% king grass + 30% concentrate. The observed variables were the consumption and digestibility of Ca and P of dairy cattle (FH). The result of research in this study that consumption of Ra was 36.10 g/head/day and Rb was 36.01 g/head/day. P consumption of Ra was 28.67 g/head/day and Rb 31.10 g/head/day (P<0.01). And then the average of Ca Digestibility in Ra was 74.28% and Rb was 80.64% (P,0.01). The digestibility of P in Ra was 75.78% and Rb was 82.62% (P<0.01). Based on the results of this study it can be concluded that the digestibility of Ca and P with a feed formulation of 35% corn forage + 35% king grass + 30% concentrate is better than the formulation of 70% corn forage + 30% concentrate.Â Keywords: Digestibility, Consumption, Ca and P, Dairy Cattle